The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1046/j.1365-2788.1998.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the PAS‐ADD Checklist for detecting psychiatric disorders in adults with intellectual disability

Abstract: The PAS-ADD Checklist is a screening instrument specifically designed to help staff recognize mental health problems in the people with intellectual disability for whom they care, and to make informed referral decisions. The instrument consists of a life-events checklist and 29 symptom items scored on a four-point scale. Scores are combined to provide three threshold scores. The crossing of any of these thresholds indicates the need for a fuller assessment. The items are worded in everyday language, making the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
386
2
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 454 publications
(406 citation statements)
references
References 10 publications
15
386
2
3
Order By: Relevance
“…The PAS-ADD Checklist is a reliable measure of psychopathology for people with ID (Moss, Prosser, Costello, Simpson, & Patel, 1998). A key informant, such as a family or staff member completed the PAS-ADD Checklist for each individual.…”
Section: Pas -Add Samplementioning
confidence: 99%
“…The PAS-ADD Checklist is a reliable measure of psychopathology for people with ID (Moss, Prosser, Costello, Simpson, & Patel, 1998). A key informant, such as a family or staff member completed the PAS-ADD Checklist for each individual.…”
Section: Pas -Add Samplementioning
confidence: 99%
“…One recent study (Hastings, Hatton, Taylor, & Maddison, 2004) summarized information on 17 major life events for 1155 individuals with ID according to informants, using the PAS-ADD checklist (Moss et al, 1998) and reported a relationship between significant life events and psychopathology, particularly in the affective domain. Another recent study (Owen et al, 2004) on 93 individuals with ID in an institutional setting used the Life Events List (LEL), a 20-item informant completed list of negative life events thought to be particularly relevant to individuals with ID in a long term residential setting.…”
Section: Introductionmentioning
confidence: 99%
“…With ten items of political participation and the narrow range of value for each item used in this study, this estimate of reliability is acceptable according to Loewenthal (1996). More discussions about reliability can be found in Cortina (1993), Goforth (2015), Hair et al (2006), Moss et al (1998), Schmitt (1996), and Streiner and Norman (2008).…”
Section: Empirical Methods and Measuresmentioning
confidence: 99%